TINGKAT KEPUASAN KONSUMEN RESTORAN PONDOK HIJAU KOTA MANADO - Arthur ., Hardyasar; Juliana R. Mandei; Joachim N.K. Dumais (AGRI-SOSIOEKONOMI, 2017)
This study aims to measure the level of customer satisfaction of green cottage restaurant viewed from the aspect of product, price, place, promotion and service. This research was conducted from February to April 2017, using primary and secondary data with sampling technique of accidental sampling method and respondents were 96 people. The method of analysis used is descriptive data analysis depicting Level of Consumer Satisfaction at Restaurant Pondok Hijau Manado City. To measure the Level of Consumer Satisfaction at Restaurant Pondok Hijau Manado City, use the Likert Scale. The result of the research showed that the perception index of customer satisfaction to the service of distribution for credit of grassroot business at Bank BRI Unit Tomohon Utara Tomoho City, Consumer Satisfaction Level of Pondok Hijau Restaurant in Manado was 76.64% and classified as Very Satisfied (SP).